ANALYSIS OF THE COLLABORATIVE MARKETING STRATEGY OF THE TOKOPEDIA AND TIKTOK SHOP PLATFORMS IN INCREASING SALES. - Sudiantini, Dian; Yunita, Evi; Fauzia, Nurul; Ramadhania, Rismawati; Yuliani, Zulfah (SENTRI: Jurnal Riset Ilmiah, 2024)
The Tiktok application itself has developed over time along with the development of technology, so that the use of Tiktok is not just about sharing information, but has become an online shopping platform. The reason is, Tiktok also presents new innovations in its own application, namely on April 17 2021 it introduced a new feature in the form of Tiktokshop. Then in September 2023, Tiktokshop was closed due to several conflicts and allegations of poor financial performance. in markets that monitor economic activity manually. Additionally, on December 11, 2023, we partnered with Tiktok to enable product sales between Tokopedia via the Tiktok application. Tokopedia and Tiktok Shop collaborate with large shipping agents in Indonesia to make it easy to check the status of goods delivery. The research method used is a qualitative research method, where this research method does not use data in the form of numbers, but data that comes from words and also from existing images. The goal of studying the results of a merger between two or more companies is to increase profitability between companies. Combining capital and assets will increase asset growth so that company profits increase. By carrying out a merger, the financial scale of a company or economic entity also becomes larger, because the business concerned becomes more productive, stronger, efficient and effective. Companies can also increase their market share by introducing new innovations and minimizing existing risks. Based on the results and discussion of the marketing strategy for the Tokopedia and Tiktok applications, it can be concluded that Tokopedia and Tiktok are effective social media in implementing marketing strategies. Advertisements implemented in the Tokopedia and Tiktok applications include advertisements, sales content, live streaming features, and others. with the aim of offering products and services to potential buyers, arousing purchasing interest and creating shopping transactions to increase sales